Pharmacological Treatments in Gambling Disorder: A Qualitative Review. (15th May 2014) - Lupi, Matteo; Martinotti, Giovanni; Acciavatti, Tiziano; Pettorruso, Mauro; Brunetti, Marcella; Santacroce, Rita; Cinosi, Eduardo; Di Iorio, Giuseppe; Di Nicola, Marco; Di Giannantonio, Massimo
Abstract : Gambling disorder (GD) is a psychiatric condition associated with both social and family costs; DSM-5 currently includes GD among addictive disorders. Despite the high burden of this condition, to date there are no treatment guidelines approved by Food and Drug Administration (FDA). Purpose of this paper is to offer a qualitative overview about the different pharmacologic agents used for the treatment of GD. Our analysis, conducted on a final selection of 75 scientific papers, demonstrates that a variety of pharmaceutical classes have been utilised, with different results. Published data, although limited by brief duration of the studies and small number of enrolled subjects, shows mixed evidence for serotonergic antidepressants, opioid antagonists, and mood stabilizers. Other compounds, such as glutamatergic agents and psychostimulants, deserve further studies.